Physical Therapy Intervention For The Hospitalized Covid-19 Patient - Dyas Nurvitasari Puspita; Anhari Achadi; Putri Karina Syafitri (Syntax Literate, 2022)
The COVID-19 pandemic was discovered in Wuhan, China that has spread throughout the world. Physical therapy also plays an important role in the recovery of patients from COVID-19 who are hospitalized and working with a multidisciplinary team. We were using the database of Scopus, ScienceDirect, and ProQuest to search for all the articles, following PRISMA guidelines. There were a total of eight articles found and included for the final of analysis. It was found that all studies have various of interventions for COVID-19 patients in the hospital, while in the ICU or critical illness and ward-based isolation with mild symptoms. Physical therapy interventions for COVID-19 hospitalized patients have a significant impact on facilitating their recovery. A various interventions, it is necessary to control a patient's condition with clinical reasoning, using the standardized PPE to reduce the risk of contagious virus